CONTROLABILIDAD EXACTA INTERNA PARA LA ECUACIÓN SEMILINEAL DEL CALOR - Cabanillas Zannini, Víctor Rafael (2008)
This work is concerned with the study of exact internal controllability problem for the semilinear heat equation with nonlinearities globally Lipschitz. Using the Minty- Brouider surjective theorem we show that the semilinear heat equation is exactly controllable in L2(Ω). For nonlinearities of the form f(y), this result was obtained by W. Liu and G. Williams [5]. Following the ideas exposed in [5] we show the same controllability result but for more general nonlinearities involving gradient f (y, y).